Re-imagining world Christianity: challenging territorial essentialism - Hof, Eleonora (Resistance and visions, 2014)
The story of a church service in Tanzania led by American missionaries is used as a tool to explore, critique and expand prevalent imaginaries of World Christianity. The first imaginary tacitly leaves out the West in World Christianity by continuing western theological normativity. Second, there is a geographic imaginary that interprets World Christianity according to continental/regional divisions. The last imaginary stresses transnational ties and their complexity and is attentive to the way in which power relationships are shaped. Territorial essentialism, which is a common strategy in the first two imaginaries, nevertheless hampers the study of World Christianity. It is defined as the naturalization of a given territory by using it as the primary lens of interpretation. Three problems connected to this strategy are discussed: territorial essentialism could give rise to a triumphalist discourse, it imagines World Christianity as a level playing field, and it can lead to considering cultures as bounded wholes. Using gender as a critical category, tropes of imagining World Christianity are challenged, shifting attention from travelling and exploration towards storytelling. Storytelling provides room for ambivalence, displacement, rupture, continuity, and the strategies of identity negotiation. In conclusion, I argue for a sustained emphasis on missionary geopolitics in the light of the continued missionary presence of the West.